Negeri Dongeng dalam Alice Trough The Looking Glass Karya Lewis Carroll - Gina Amalia Rahmah Dewi (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
This research is entitled "The Fairytale Country in the Novel Alice Through The Looking Glass by Lewis Carroll". This study aims to identify and explain the setting of the place in the novel Alice Through The Looking Glass. In analyzing the setting of the place, the author uses the theory of Aminuddin (2013). The research method used in this research is descriptive qualitative and uses data collection techniques to observe and record. The approach in this study uses an objective approach because the analysis in this study only focuses on the intrinsic elements of the novel. Based on the results of this research, it is found that the setting of the place is from two worlds, namely the real world that Alice lives in and the world of mirrors. All of the place setting data found consisted of houses, parks, forests, train, shops, and boats. However, the setting where the house is found by the author is in the real world where Alice lives and the world of mirrors.